Modelo de evolución crediticia para minimizar el índice de morosidad en la cooperativa de ahorro y crédito SUMAK SAMY LTDA., de la ciudad de Ambato, provincia de Tungurahua. - Caiza Chaluis, José Israel (2020)
The purpose of this research work is to design a credit assessment model to minimize the late payment rate in the Credit Union “SumakSamy Ltda.”, of the Ambato city, Tungurahua Province. Due to the inadequate credit evaluation that affects the credit portfolio of said institution. This research was scientifically based on credit assessment models in order to achieve the appropriate study, the current situation of the cooperative was also diagnosed through the financial statements. The entity shows that for 2019 the composition of assets was 94.20%, non-current assets of 3.83%, and other non-current assets was 1.94%. The current liability was 85.67% and the equity was 14.33%, for this investigation a mixed methodology with qualitative and quantitative approach of descriptive nature was used, the information was collected through the survey and observation sheet, it was carried out a horizontal and vertical analysis of the financial statements. In this context, the weaknesses were evident when evaluating the credits, one of the causes that was most evident is the inadequate evaluation of credits caused by the risk. For which the improvement is proposed based on the design of the 5C’s model of credit that prevents late payment: character, capacity, conditions, collateral and capacity. Evaluating these concepts will improve the credit management of the Cooperative. This tool will help to examine the different types of credits, as well as establish the income and expenses of the clients and their credit history. In conclusion, it is established that this proposal will improve the business area of the cooperative